If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-3)=-2(x-4)
We simplify the equation to the form, which is simple to understand
4(x-3)=-2(x-4)
Reorder the terms in parentheses
+(+4x-12)=-2*(x-4)
Remove unnecessary parentheses
+4x-12=-2+*(+x-4+)
Reorder the terms in parentheses
+4x-12=+(-2x+8)
Remove unnecessary parentheses
+4x-12=-2x+8
We move all terms containing x to the left and all other terms to the right.
+4x+2x=+8+12
We simplify left and right side of the equation.
+6x=+20
We divide both sides of the equation by 6 to get x.
x=3.33333333333
| ax-3b+7c=0 | | 12=10+12 | | ax-3b=7c | | -1(x+2)=5(x+1) | | 2x^2-3=-53 | | 5x^2=38x+16 | | -10-5x=5 | | 3(x-1)=4(x+2) | | -9-2x=17 | | -9-2x=16 | | 4y+10y=360+15-30y | | x+7=19-2x | | x+2x+3=x+15 | | 28+x=11 | | 3x+11=-4 | | 7x+15=-6 | | 10x-12+10=18+20 | | 3x+5+2x=100 | | y+32=13 | | 5t-7=11-t | | 8+17=9 | | -7x-12=44 | | x^2-3x=-0.5 | | 72+13= | | 3[3(4x-7)-4(2x-7)]=11x+25 | | 3s+5p=tp-5 | | 5[4+6(4x-2)]=6x-838 | | x^2-3x+2.25=1.75 | | 9+8y-4=9y+53-7y | | 6x-10x-5=7 | | 11+5x=-34 | | -8x=8 |